Washback of the performance-based test of reading for EFL learners - Wiyaka Wiyaka (Universitas Islam Sultan Agung, 2020)
The effect of tests on the teaching and learning, generally known as washback, has been recognized by scholars for a long time. However, studies on washback are usually addressed for high-stakes testing. This study investigates the washback effect of low-stakes test namely performance-based test used in measuring reading skills. Such a test is low stakes because it does not bring about serious consequence on the part of the students. The subjects of the research were 10 English teachers and 50 students of junior high schools in Semarang, Central Java, Indonesia. Data were collected through semi-structured interview and a questionnaire for both the teachers and students. The results showed that performance-based test gives positive effect in reading for the EFL learners in the areas of: students’ enthusiasm in reading, reducing boredom in reading, students’ curiosity on reading text content, and students’ improvement on higher-order thinking skills. To the teachers it affects the areas of teaching methods, teaching materials, and time allotment.